Implementation Of The AHP Method And Decision Table To Determine The Problem Student - Heribertus Ary Setyadi; Agus Kristianto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
o far, the selection of types and weight of student violations is rather difficult to be done by the college. Sometimes a student has a good performance in terms of lectures, but on the other hand less in terms of behavior or attitude compared with other students and vice versa. It is necessary to develop assessment methods to conduct selection and evaluation of the students, especially those indicated problematic to be evaluated and handled in a more structured manner. In this study created a system that produces a system that supports decision-making to determine students who have problems and need attention as well as special guidance objectively. The system is created by using AHP method which is one of the methods in decision support system and decision table which is one method in data mining. The criteria used are value of achievement index, length of study, duration of not active as student, amount of absenteeism, payment of SPP, alcohol use, drugs and fighting. The AHP method is used to determine the weight of each criterion according to the input of the interest ratio. In addition to weight, the results of the AHP method also determine the classification of actions forproblem students. Decision table generates referrals according to the classification produced by the AHP method.The system can describe the AHP process at each step in the form of a matrix so that it can be studied and evaluated the truth of each step on the method used. Keywords: AHP, Decision Table, Problematic Students.